Time-dependent versus State-dependent Pricing: A Panel Data Approach to the Determinants of Belgian Consumer Price Changes - Luc Aucremanne; Emmanuel Dhyne (National Bank of Belgium, 2005)
Using Logistic Normal regressions, we model the price-setting behaviour for a large sample of Belgian consumer prices over the January 1989 - January 2001 period. Our results indicate that time-dependent features are very important, particularly an infinite mixture of Calvo pricing rules and truncation at specific horizons. Truncation is mainly a characteristic of pricing in the service sector where it mostly takes the form of annual Taylor contracts typically renewed at the end of December. Several other variables, including some that can be considered as state variables, are also found to be statistically significant. This is particularly so for accumulated sectoral inflation since the last price change. Once heterogeneity and the role of accumulated inflation are acknowledged, hazard functions become mildly upward-sloping, even in a low inflation regime. The contribution of the state-dependent variables to the pseudo-R² of our equations is, however, not particularly important.
Keywords: C23; C25; D40; E31; 330; consumer prices; time-dependent pricing; state-dependent pricing; Calvo model; Truncated Calvo model; Taylor contracts; Preisniveau; Preiselastizität; Preisrigidität; Schätzung; Belgien; Logit-Modell